2021
DOI: 10.1111/all.14852
|View full text |Cite
|
Sign up to set email alerts
|

IgE antibodies increase honeybee venom responsiveness and detoxification efficiency of mast cells

Abstract: Background: In contrast to their clearly defined roles in allergic diseases, the physiologic functions of Immunoglobulin E antibodies (IgEs) and mast cells (MCs) remain enigmatic. Recent research supports the toxin hypothesis, showing that MCs and IgErelated type 2 immune responses can enhance host defense against certain noxious substances, including honeybee venom (BV). However, the mechanisms by which MCs can interfere with BV toxicity are unknown. In this study, we assessed the role of IgE and certain MC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…A puzzling finding was the detection of neonatal fecal sIgE directed to an array of environmental allergens such as cockroach (Bla g 1, Bla g 2, Bla g 4, Bla g 5, Bla g 9, Per a 7), the tick Argas reflexus (Arg r 1), the fish parasite Anisakis simplex (Ani s 1), and insect venoms (Api m 1, Api m 10, Ves v 1, Ves v 5, Pol d 5). We speculate that such sIgE responses might relate to a broader function of immune defense of the mast cell-IgE couple, as suggested by recent findings 23,24 , harnessing the ability of maternal, and presumably fetal, sIgE to sensitize fetal mast cells 6 .…”
Section: Discussionmentioning
confidence: 62%
“…A puzzling finding was the detection of neonatal fecal sIgE directed to an array of environmental allergens such as cockroach (Bla g 1, Bla g 2, Bla g 4, Bla g 5, Bla g 9, Per a 7), the tick Argas reflexus (Arg r 1), the fish parasite Anisakis simplex (Ani s 1), and insect venoms (Api m 1, Api m 10, Ves v 1, Ves v 5, Pol d 5). We speculate that such sIgE responses might relate to a broader function of immune defense of the mast cell-IgE couple, as suggested by recent findings 23,24 , harnessing the ability of maternal, and presumably fetal, sIgE to sensitize fetal mast cells 6 .…”
Section: Discussionmentioning
confidence: 62%
“…The MC enzymes can most likely also play an important role in facilitating the influx of inflammatory cells by cleavage of connective tissue components to loosening up the compact connective tissue and also to inhibit coagulation when blood vessels open for influx of antibodies, complement and inflammatory cells. To this should be added the potent effects on numerous venoms from snakes, scorpions, Gila monster and bees ( 78 , 79 ). The effect on venoms seems to be very complex and involves all three major classes of the mast cell proteases, the chymase, the tryptase and the CPA3.…”
Section: Discussionmentioning
confidence: 99%
“…Venoms delivered by snake bites, scorpion stings or bee and wasp stings are generally appearing in the skin. Several elegant studies have shown the potent action of the different MC enzymes on these venoms resulting in their inactivation (42,(77)(78)(79)(80). The venoms also act directly on the MCs by inducing degranulation (80).…”
Section: Inactivation Of Venomsmentioning
confidence: 99%
“…Indeed, mice lacking mast cell and/or basophils were unable to acquire venom resistance after immunization 99 . Furthermore, local FcεRI‐IgE FAP mast cell degranulation enhanced venom detoxification 99,100 thanks to proteases contained in their granule such as carboxypeptidase 3 and chymase, 101,102 which degrade venom peptides (sarafotoxin and helodermin, respectively) with structure similarity to endogenous mammalian peptide (endothelin 1 and vasoactive intestinal peptide, respectively) 103 . Interestingly in those mice model of envenomation, mast cell, basophil, or even innate lymphoid cells type 2 were not required to induce IgG1 and IgE immunization against venom antigen 98,99 .…”
Section: Potential Roles Of Immunoglobulin E In Health and Non‐allerg...mentioning
confidence: 99%